Requirements for access to the sacrament of marriage? Dogmatic perspective - Martínez Oliveras, Carlos (Estudios Eclesiásticos. Revista de investigación e información teológica y canónica, 2016)
The requirement of faith for the celebration of the sacraments is an issue that has always been present in the theological debate. The peculiar characteristic of marriage as an anthropological reality elevated to the dignity of a sacrament confers an unique situation because faith, joined with the intention, set the complex and inseparable binomial contract-sacrament and, therefore, the validity and fruitfulness of marriage. Only an adequate pastoral-theological approach that combines the theological faith and personal faith will assure an adequate sacramental union. Thus, the marriage contracted between two baptized will be able to reflect the love of Christ for His Church and live a spousal mature.
Keywords: Faith; intention; marriage; Church; contract-sacrament; Familiaris Consortio.